2019
DOI: 10.1101/568501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An engineered monomer binding-protein forα-synuclein efficiently inhibits the proliferation of amyloid fibrils

Abstract: Removing or preventing the formation of α-synuclein aggregates is a plausible strategy against Parkinson's disease. To this end we have engineered the β-wrapin AS69 to bind monomeric α-synuclein with high affinity. In cultured cells, AS69 reduced the occurrence of α-synuclein oligomers and of visible α-synuclein aggregates. In flies, AS69 reduced α-synuclein aggregates and the locomotor deficit resulting from α-synuclein expression in neuronal cells. In a mouse model based on the intracerebral injection of pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We expect that the release of long-range contacts with the C-terminus leads to exposure of the N-terminus and the NAC region, observed in WT and A53T aSyn, to be a major factor influencing aSyn aggregation kinetics. Previous experiments have shown that the N-terminus of aSyn may modulate aSyn aggregation; altering sequence, cross-linking specific residues and targeting binding proteins to the N-terminus leads to variation in aggregation kinetics [63][64][65][66][67][68] . Previous studies have shown mutant aSyn have altered long-range interactions compared to WT aSyn 35,[69][70][71][72] .…”
Section: No Of Camentioning
confidence: 99%
“…We expect that the release of long-range contacts with the C-terminus leads to exposure of the N-terminus and the NAC region, observed in WT and A53T aSyn, to be a major factor influencing aSyn aggregation kinetics. Previous experiments have shown that the N-terminus of aSyn may modulate aSyn aggregation; altering sequence, cross-linking specific residues and targeting binding proteins to the N-terminus leads to variation in aggregation kinetics [63][64][65][66][67][68] . Previous studies have shown mutant aSyn have altered long-range interactions compared to WT aSyn 35,[69][70][71][72] .…”
Section: No Of Camentioning
confidence: 99%
“…Relaxation experiments. For all samples, 15 N transverse relaxation (R 2 ) experiments were measured from a series of HSQC-based 2D 1 H-15 N spectra using the Carr-Purcell-Meiboom-Gill pulse sequence with varying relaxation delays: 15 N-Ac-αS sonicated fibrils and 15 N-Ac-αS monomers at 800 MHz-0, 8,16,16,32,64,128,192,256, and 320 ms; 15 N-Ac-αS off-pathway oligomers and 15 N-Ac-αS monomers at 800 16,32,48,64,96,128,160,192,224, and 256 ms; 15 N-Ac-αS monomers alone or in the presence of sonicated fibrils at 700 MHz-0, 8,16,32,32,64,128,192,256, 320 ms; and 15 N-Ac-αS monomers alone or in the presence of offpathway oligomers at 700 16,32,48,64,96,128,160,192,224, and 256 ms. 15 N-R 2 rates were measured by fitting a single exponential decay function to peak intensities of the decay curves for each residue. Where reported, ΔR 2 is the difference between the measured 15 15 N-Ac-αS monomer at 800 MHz-0, ±0.5, ±1, ±2, ±4, ±8, ±18, and ±30 kHz; 350 µM 15 N-Ac-αS sonicated fibril at 800 MHz-0, ±0.5, ±1, ±2, ±4, -8, +18, and ±30 kHz; and 90 µM 15 N-Ac-αS monomer in the absence or presence of 90 µM Ac-αS fibril seed at 700 MHz: 0, ±0.5, ±1, ±4, and ±30 kHz.…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…Previous approaches to inhibit different aspects of amyloid fibril seeding have largely targeted the structured amyloid core. Such methods include using chaperones to block fibril ends or fibril surfaces (9), treating with natural products that promote fibril clustering to reduce fibril fragmentation and hide binding sites for monomer addition (14,15), and creating high affinity interactions with amyloidogenic monomers to sequester monomers from self-assembly (16). However, all of these approaches introduce foreign molecules and can only interfere with single microscopic steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches describe structures gained via recombinant means under in vitro conditions [2][3][4][5]7,9,10 . Others have employed the use of lipids during in vitro experiments, since this is critical to αS function in situ 6,[11][12][13][14][15][16][17] . More recent studies are emerging in which aggregates of αS from specific neurodegenerative diseases and key regions of the brain are isolated in small quantities 8,18 .…”
Section: Introductionmentioning
confidence: 99%